The study of the effects of parental factors on the educational outcome among children in Filipino households - Enriquez, Nina Samantha U. (School of Economics, University of the Philippines Diliman, 2019)
Recent developments in children_s academic performances have found that parental factors have significant effects on a child_s educational attainment. However, existing research dwells minimally on the mechanisms which explain the association between parental factors and schooling outcomes in developing countries. The objective of this research is to identify parental indicators, such as employment status, parental style, and educational attainment, which may serve as current predictors of students who are at risk of dropping out of high school. This study uses the Cebu Longitudinal Health and Nutrition Survey (CLHNS) dataset, which comprises of 28,000 households and includes data on the mothers, their spouses, and children. The participants were interviewed in 1994 regarding their health status, academic performance, and household relationships. The index children were then asked a series of follow_up questions during 1998, 2002, 2005, and 2009. Data was analyzed using Cox proportional hazards model and survival analysis by examining the index child_s age of dropout. The results indicate that a combination of both parental and economic factors are strong predictors of children at risk of dropout. In particular, the at_risk students decreases among children whose parents value education. Additionally, the risk of dropout is also reduced among children who belong to smaller households and who have easier access to education.